Sensory Study and Financial Feasibility Analysis of Alpinia galangal Fish Shredded Products - Fadli Alamsyah; Dewi Sartika; Sussi Astuti; Wisnu Satyajaya; Sri Hidayati; Puan Mutia Ayunisa (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Spices have always been a part of Indonesia's culinary culture. One of the spices that has high economic value and efficacy is galangal. Therefore, testing of bioactive compounds and the effect of making shredded spice fish with the addition of various concentrations of galangal needs to be further investigated in terms of sensory quality and financial feasibility. This study aims to determine the bioactive components in galangal spice, determine the best concentration of galangal addition in shredded spiced fish products, and determine the financial feasibility. The research was conducted by making galangal spice and shredded spiced fish at IDAEZ Group MSMEs. Subsequently, the galangal spice was tested for bioactive compound (GC-MS) and then, sensory tests were carried out on shredded fish spices mixed with galangal spices (1%, 2%, 3%). After that, the financial feasibility analysis was calculated. The results obtained showed that there were four main components in galangal spice, such as 5-Eicosenen, (E)-, n-Hexadecanoic acid, oleic acid, and 9-Octadecenoic acid (Z)-, oxiranylmethyl ester. Meanwhile, the best concentration of shredded spice fish was found in treatment P3 (addition of 3% galangal). Lastly, the shredded spice fish was found to be viable with an income of IDR 427,547 per production. Keywords: Financial feasibility, GC-MS, Galangal, Sensory.